Traumatic Brain Injury and Early Onset Dementia in Post 9-11 Veterans. (16th April 2022) - Kennedy, Eamonn; Panahi, Samin; Stewart, Ian J.; Tate, David F.; Wilde, Elisabeth A.; Kenney, Kimbra; Werner, J. Kent; Gill, Jessica; Diaz-Arrastia, Ramon; Amuan, Megan; Van Cott, Anne C.; Pugh, Mary Jo
ABSTRACT: Objectives: To assess traumatic brain injury (TBI)-related risks factors for early-onset dementia (EOD). Background: Younger Post-9/11 Veterans may be at elevated risk for EOD due to high rates of TBI in early/mid adulthood. Few studies have explored the longitudinal relationship between traumatic brain injury (TBI) and the emergence of EOD subtypes. Methods: This matched case-control study used data from the Veterans Health Administration (VHA) to identify Veterans with EOD. To address the low positive predictive value (PPV = 0.27) of dementia algorithms in VHA records, primary outcomes were Alzheimer's disease (AD) and frontotemporal dementia (FTD). Logistic regression identified conditions associated with dementia subtypes. Results: The EOD cohort included Veterans with AD (n = 689) and FTD (n = 284). There were no significant demographic differences between the EOD cohort and their matched controls. After adjustment, EOD was significantly associated with history of TBI (OR: 3.05, 2.42–3.83), epilepsy (OR: 4.8, 3.3–6.97), other neurological conditions (OR: 2.0, 1.35–2.97), depression (OR: 1.35, 1.12–1.63) and cardiac disease (OR: 1.36, 1.1–1.67). Conclusion: Post-9/11 Veterans have higher odds of EOD following TBI. A sensitivity analysis across TBI severity confirmed this trend, indicating that the odds for both AD and FTD increased after more severe TBIs.